Application of farmyard manure and vermi-compost on vegetative and generative characteristics of Jatropha curcas - Saroj Mishra, Ashwani Kumar, Satyawati Sharma (Journal of Phytology, 2009)
This study was conducted to investigate the effect of FYM and Vermi-compost on: i) biomass yield of vegetatively propagated Jatropha curcas and ii) physical characteristics of Jatropha seeds. Various vegetative and generative characteristics of Jatropha (survival %, shoot length, shoot diameter, number of branches, seed yield and oil content) in response to the treatments were evaluated under field conditions. The results showed that addition of vermicompost significantly increased plant survival, plant height, stem diameter, number of branches/plant, number of seeds/plant and oil content (6.76% & 19.21%) over FYM and control. Vermicompost also played an important role in increasing oil content by improving physical characteristics of Jatropha seeds. We conclude Jatropha raised through cuttings on vermicompost performed better with respect to biomass yield over FYM and untreated soil.